Studi Kelayakan Lokasi Pengembangan Proyek Properti Perumahan Planet Green Tambora Terhadap Minat Beli Konsumen - Hammam Rofiqi Agustapraja; Moh Anang Maulana (P3M- Politeknik Negeri Kupang, 2021)
The development of the population in the city of Lamongan continues to grow rapidly, this indirectly affects the residential place that is home. Strategic residential locations are currently needed to choose a place to stay. The choice of the wrong location can result in poor consumer purchase interest. This research aims to determine the effect of the feasibility of housing locations on consumer buying interest partially. The analytical method used in this study is the validity test, reliability test, normality test, determination test (r), and t-test. Data obtained from distributing questionnaires in the form of questionnaires distributed at the research location. The results achieved in the study showed the results of the validity test and the reliability test showed valid and reliable, the error rate of 95% or 0.05 resulted in the determination test results resulting in 81% of the variable variation in consumer purchase satisfaction can be explained by the variable feasibility of the location. While the t-test produced results x1 = 3,426, x2 = 5,886, x3 = 3,424, from the test results it can be interpreted that the feasibility of the location consisting of the conditions of the region x1, land use x2, health and ease of x3 affect the consumer buying interest.